Postfire changes of inner bark in Scots pine stems - V. V. Stasova; O. N. Zubareva; G. A. Ivanova; A. B. Bazhenova (Сибирский лесной журнал, 2020)
In studies of tree fire damages, attention is usually paid to growth and development of wood (xylem). But for tree vitality a very important role belongs to the tissues outside the cambium – phloem (inner bark). The object of this work was to continue the study of anatomical features and chemical composition of inner bark of Scots pine Рinus sylvestris L. stems with different fire scars after prescribed fires of different intensity. The fire experiments were carried out in pine stands in Lower Angara river region of the Angara provenance, Krasnoyarsk Krai, Central Siberia. Anatomic analyses of stem cores of experimental and control trees were carried out by the methods of light microscopy and histochemistry. It was shown that eight years after the low-intensity and 13 years after the medium- and high-intensity fires, the thickness of inner bark increased in all the studied trees, as well as in the control. Moreover, a decrease in the number of annual phloem layers between the cambium and periderm was noted. The number of cells in the radial row of the conducting phloem after a low-intensity fire was almost the same in inner bark of trees damaged by fire and not damaged (control), after a medium-intensity fire, it decreased with an increase of fire scars square, after a high-intensity fire a tendency to increase in trees with severe fire damage was noted. The content of axial parenchyma was found to increase with increase of stem fire damage in trees after a low-intensity fire and decreased after fires of medium and high intensity. There was a tendency to an increase in the frequency of phloem rays in tree trunks with an increase of stem fire damage after a low-intensity fire; after medium-high and high-intensity fires any trends could not be identified. Distribution and amount of starch in the ray and axial parenchyma in the inner bark of all model trees was found to be almost the same. A tendency to increase the accumulation of callose in non-conductive phloem with an increase in the intensity of fire impact to ...